Effect of Strain Rate on the Mechanical Properties of Cu/Ni Clad Foils - Haiyang Wang (MDPI AG, 2021)
The performance of clad foils in microforming deserves to be studied extensively, where the strain rate sensitivity of the clad foil concerning the forming performance is a crucial factor. In this paper, the strain rate sensitivity of the mechanical properties of coarse-grained (CG) Cu/Ni clad foils in the quasi-static strain rate range (<semantics><mover accent="true">ε˙</mover>=10−4 s−1~10−1<mtext> </mtext>s−1</semantics>) is explored by uniaxial tensile tests under different strain rates. The results show that the strength and ductility increase with strain rate, and the strain rate sensitivity m value is in the range of 0.012~0.015, which is three times the value of m for CG pure Cu. The fracture morphology shows that slip bands with different directions are entangled in localized areas near the interface layer. Molecular dynamics simulations demonstrate the formation of many edged dislocations at the Cu/Ni clad foils interface due to a mismatch interface. The improved ductility and strain rate sensitivity is attributed to the interaction and plugging of the edged dislocations with high density in the interface layer. Additionally, the influence of size effect on mechanical properties is consistently present in the quasi-static strain rate range. This paper helps to understand the strain rate sensitivity of CG clad foils and to develop clad foils in microforming processes.